Inventarisasi Data Keruangan Melalui Pemetaan Partisipatif Batas Desa Langlang Kecamatan Singosari Kabupaten Malang - Agus Purnomo; Idris; Bayu Kurniawan (Jurnal Pemberdayaan Masyarakat, 2023)
Langlang Village is a village in Singosari District with a strategic location close to the main route to Batu City and unique umbul potential. The aim of the service activity is to inventory spatial data through mapping Langlang Village. This service activity method uses a Rural Participatory Appraisal approach. The design of mapping activities in Langlang consists of 3 stages: the FGD stage, data collection training stage, and information presentation stage. Characteristics of participatory mapping include a) involving all members of the community, b) the theme, objectives, and process of implementing the mapping are determined by the community, c) the map produced is aimed at the interests of the community, d) most of the information contained in the map comes from local knowledge, and e) the community determines the use of the resulting map. Community service activities produce village maps containing geospatial information in the area. The use of maps is used as a guide in regional planning by local village officials and the community, providing community understanding and knowledge in understanding the characteristics of the region and its administrative boundaries.